An Innovative Modification of an Old Radiosurgery System - Kandasamy, Regunath; Sim, Sze Kiat; Nik, Ruzman ([Kubang Kerian, Kelantan, Malaysia] : School of Medical Sciences, Universiti Sains Malaysia, 2013)
Hospital Universiti Sains Malaysia (HUSM) is credited as one of the very first centres to offer radiosurgical services in the country. Up until February 2011, a total of 167 patients have received stereotactic radiosurgery and stereotactic radiotherapy treatment for a wide spectrum of neurosurgical conditions. Radiosurgery services in USM commenced in 2001 with the purchase of a medical linear accelerator (Siemens, Primus) complimented by treatment cones, head rings, localiser system and a workstation for planning from Radionics. The Stereotactic Radiosurgery (SRS) service in USM proved to be a vital one with patients being referred to us from all corners of the country including from East Malaysia (1,2).